(untitled) (Raparin Journal of Humanities (RJH), 2025)
Climate change has recently shown signs of global warming due to increased human activities and burning of fossil fuels, which has led to increased concentrations of greenhouse gases (GHGs). Climate change has negative effects on the global climate generally and the Middle East and Iraq especially. Climate change also impacts on research areas by increasing temperatures and decreasing precipitation. This paper analyses time and direct temperature with the distribution of the yearly and seasons in Dukan district during research studies between (2003-2022). This research study attempts to answer these questions: is it a change in temperature in the study area? Is the change of temperature direction by increase or decrease? What are the factors for changes in temperature and distribution yearly and seasons in the region? The methodology of the research is using inductive and analysis with collecting data from the weather stations of the Dukan area using (SPSS, ArcGIS, and Excel) to find the relationship between temperature and other elements of climate. The research got some results: changes in climate were increased during the study area in the maximum and minimum temperature and average temperature in the seasons and average years.